Energy in the Americas; Energy in the Americas Critical Reflections on Energy and History; Critical Reflections on Energy and History - Kiddle, Amelia M. (Energy Histories, Cultures, and Politics, 2021)
Understanding the history of energy and the evolving place of energy in society is essential to facing the changing future of energy production. Across North and South America, national and localized understandings of energy as a common, public, or market good have influenced the development of energy industries. Energy in the Americas brings the diverse energy histories of North and South American nations into dialogue with one another, presenting an integrated hemispheric framework for understanding the historical constructions of contemporary debates on the role of energy in society. Rejecting pat truisms, this collection historicizes the experiences of producers and policymakers and assesses the interplay between environmental, technological, political, and ideological influences within and between countries and continents. Breaking down assumptions about the evolution of national energy histories, Energy in the Americas broadens and opens the conversation. De-emphasizing the traditional focus on national peculiarities, it favours an international, integrated approach that brings together the work of established and emerging scholars. This is an essential step in understanding the circumstances that have created current energy policy and practice, and the historical narratives that underpin how energy production is conceptualized and understood.